Investigación y gestión de iniciativas innovadoras en educación: aspecto metodológico - Odarchenko, Veronika; Pukhno, Svitlana; Bondar, Ihor; Skomorovska, Iryna; Ulyanova, Victoria (My University, 2024)
In the article, the degree of development of the problem of innovation-oriented training of teachers in additional professional education in theory and practice is determined, a systematic view of the object and subject of research in the context of the leading trends in the development of education is formed. On the basis of a comparative analysis of the scientific innovations presented, the essence of the concept of "pedagogical innovation" has been clarified, the specifics of innovation-oriented education have been identified and substantiated. The conceptual foundations of innovatively oriented pedagogical management have been developed. Methodological approaches and organizational-pedagogical foundations of training in the professional education of teaching staff for pedagogical management have been developed
Keywords: педагогічна інновація; педагогічні основи; потреби професійної освіти; педагогічне управління; pedagogical innovation; pedagogical foundations; professional education needs; pedagogical management